The Effect of Fertility on Female Labor Supply in a Labor Market with Extensive Informality - Semih Tumen; Belgi Turan (Institute of Labor Economics (IZA), 2020)
This paper presents new evidence on the causal relationship between fertility and female labor supply. We particularly focus on how informal employment affects post-fertility labor supply behavior of mothers. We employ an instrumental variable strategy based on an unused data source for twin births in Turkeyâ exteuro”a large developing economy with extensive labor informality. We find that fertility causally affects female labor supply. After the first twin birth, female labor supply declines significantly and the ones who drop out of the labor force are mostly the informally employed women. Following further increases in family size introduced by multiple second and third births (i.e., unanticipated increase from 1 kid to 3 kids, and from 2 kids to 4 kids), formally employed females start dropping out of the labor force and hours of work decline. Wages and job search intensity also decline for females as fertility increases. We also investigate the impact of fertility on labor supply of fathers. Unlike females, males increase their labor supply, which mostly comes from the increase in informal employmentâ exteuro”possibly due to a decline in reservation wages. Accordingly, wages decline, hours of work increase, and job search activity shifts from formal to informal search methods for males. Overall, these results suggest that informally employed women tend to quickly drop out of the labor force after giving birth. Fathers, on the other hand, become more likely to accept inferior, low-pay, and informal job offers as fertility goes up. The results are robust to using alternative IV specifications based on sex composition of children.
Keywords: J21; J22; J13; J31; 330; job search; instrumental variables; twin births; informal employment; labor supply; fertility